Studi komparatif strategi pembelajaran matriks & quick on the draw (QD) untuk meningkatkan hasil belajar siswa - Azhari, Muhammad Hafizh; Safitri, Nabella Putri Rama; Norhafizah, Norhafizah; Ulanhar, Salma Nida; Zaini, Muhammad; Putra, Aminuddin Prahatama; Fajeriadi, Hery; Sari, Normila; Roziah, Mida Laisani (Journal of Bio-Creaducation, 2025)
The learning outcomes of students in the concepts of the circulatory system at MTsN Anjir Muara Kota Tengah and the locomotor system at SMP Negeri 1 Takisung have shown low completeness, below the standard of ≤ 60% and 42.30%, respectively. To address this issue, this study implemented two innovative methods: the cooperative learning model Quick on The Draw and the memory matrix strategy, aiming to improve learning outcomes, student activity, teacher activity, and responses to both methods. The Quick on The Draw cooperative learning model was conducted in two cycles, each consisting of two meetings. Results indicated that this method successfully enhanced student learning outcomes, with classical completeness increasing from 72.72% in cycle I to 90.91% in cycle II. Student engagement improved significantly, as evidenced by increased participation in reading, discussions, and answering questions. Teacher management of learning also improved from a "fairly good" to a "good" category, with 100% of students expressing that the method made learning more engaging and enjoyable. Similarly, the memory matrix strategy was implemented in two cycles, showing a 7.3% increase in learning outcomes, with average scores rising from 83.03 to 87.92. Student activities in reading, discussing, and summarizing improved, although teacher guidance decreased. Overall, both methods proved effective in enhancing student learning outcomes and creating a more active and enjoyable learning environment.Hasil belajar siswa pada pembelajaran konsep sistem peredaran darah di MTsN Anjir Muara Kota Tengah dan sistem gerak di SMP Negeri 1 Takisung menunjukkan ketuntasan yang masih rendah, yaitu di bawah standar, yaitu ≤ 60% dan 42,30%. Untuk mengatasi masalah ini, penelitian ini menerapkan dua metode inovatif: pembelajaran kooperatif tipe Quick on The Draw dan strategi matrik ingatan, dengan tujuan untuk meningkatkan hasil belajar, aktivitas siswa, aktivitas guru, serta respon terhadap kedua metode tersebut. Pembelajaran kooperatif tipe Quick on The Draw dilaksanakan dalam dua siklus, masing-masing terdiri dari dua kali pertemuan. Hasil penelitian menunjukkan bahwa metode ini berhasil meningkatkan hasil belajar siswa, dengan ketuntasan klasikal meningkat dari 72,72% pada siklus I menjadi 90,91% pada siklus II. Aktivitas siswa juga mengalami peningkatan yang signifikan, terlihat dari peningkatan dalam membaca bahan ajar, berdiskusi, dan aktif menjawab pertanyaan. Respon siswa terhadap pembelajaran ini sangat positif, dengan 100% menyatakan setuju bahwa metode ini membuat kegiatan belajar lebih menyenangkan. Di sisi lain, strategi matrik ingatan juga menunjukkan peningkatan hasil belajar dari siklus I ke siklus II sebesar 7,3%, dengan nilai rata-rata meningkat dari 83,03 menjadi 87,92. Secara keseluruhan, kedua metode pembelajaran ini terbukti efektif dalam meningkatkan hasil belajar siswa dan menciptakan suasana belajar yang lebih aktif dan menyenangkan.